Answer:
[tex]\displaystyle\frac{3\sqrt{3}}{4}[/tex]
Explanation:
Given,
& is defined,
[tex]a \& b = \displaystyle\frac{\sqrt{a b + a}}{\sqrt{a b - b}}[/tex]
If a = 9, b = 2,
[tex]9 \& 2 = \displaystyle\frac{\sqrt{(9)(2)+ (9)}}{\sqrt{(9)(2)- 2}}[/tex]
[tex] = \displaystyle\frac{\sqrt{18 + 9}}{\sqrt{18 - 2}}[/tex]
[tex]= \displaystyle\frac{\sqrt{27}}{\sqrt{16}}[/tex]
[tex]=\displaystyle\frac{\sqrt{9}\sqrt{3}}{4}[/tex] ( ∵√16 = 4 )
[tex]=\displaystyle\frac{3\sqrt{3}}{4}[/tex] ( ∵ √9 = 3 )
∵ Further simplification is not possible,
Hence, the required simplified form is,
[tex]\displaystyle\frac{3\sqrt{3}}{4}[/tex]